2005
DOI: 10.1007/bf02893042
|View full text |Cite
|
Sign up to set email alerts
|

Altered pattern of lipids in plasma and erythrocyte membranes of rheumatoid arthritis patients

Abstract: The present study has investigated the levels of lipids, lipoprotein cholesterol (HDL and LDL cholesterol), thiobarbituric acid reactive substances (TBARS) and vitamin E in plasma and erythrocyte membranes of twenty two clinically diagnosed adult rheumatoid arthritis patients and an equal number of age matched healthy subjects. The levels of lipids and lipoprotein cholesterol were markedly reduced in patients with rheumatoid arthritis as compared to healthy subjects. The altered lipid pattern may be related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
(9 reference statements)
4
2
0
Order By: Relevance
“…16 In other diseases, serum lipid pattern, phospholipid fatty acid composition, and fatty acid unsaturation index, vitamin E content and LPO correlated with the composition and structure of erythrocyte membranes. 17,18 This matches our own fi ndings. However, in this context, it must be mentioned that -different from other diseases -thalassemic hemoglobin plays a deleterious role in the destruction of RBC membranes.…”
Section: Transfusion-dependent Patientssupporting
confidence: 90%
“…16 In other diseases, serum lipid pattern, phospholipid fatty acid composition, and fatty acid unsaturation index, vitamin E content and LPO correlated with the composition and structure of erythrocyte membranes. 17,18 This matches our own fi ndings. However, in this context, it must be mentioned that -different from other diseases -thalassemic hemoglobin plays a deleterious role in the destruction of RBC membranes.…”
Section: Transfusion-dependent Patientssupporting
confidence: 90%
“…Both possibilities suggest a condition of oxidative stress is present in whole blood of RA patients. This is in agreement with reports of increased ROS and biomarkers of oxidative damage in either plasma and/or erythrocytes of RA patients . To our knowledge no reports exist on oxidative stress in the whole blood of RA patients and these studies provide limited information on the true redox status of RA patients .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown an increased level of thiobarbituric acid reactive substances (TBARS) (6.58 ± 0.49, P < 0.001) in RA patients 48 . The present study results show significant reduction in levels of TBARS (a marker of oxidative stress) ( P < 0.01) after drug treatment (Table 2).…”
Section: Discussionsupporting
confidence: 74%